The Opinions of Teachers toward the Skills of School Administratorsin the 21st Century at the United - Wantakaew, Rattana; Silanookit, Chonmanee (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This research aimed to study and compare teachers’ opinions on the administrative skills of the school administrators in the 21st century, the schools in the group of United Campus Ratchayothin under the Secondary Educational Service Area Office 2 which is classified by educational level and work experience. The sample group used in this research is 234 teachers in the group of United Campus Ratchayothin under the Secondary Educational Service Area Office 2. Tools used for data collection is a 5-level estimation scale questionnaire. That has a consistency value of .80 to 1.00 with a confidence value of 0.906. The statistics used in this research were frequency, percentage, mean, standard deviation, t-test, and One-Way ANOVA. The results of the research were as follows: 1) The opinions of the teachers on the administrative skills of the school administrators in the 21st century, schools in the group of United Campus Ratchayothin under the Secondary Educational Service Area Office 2. In overall level, it was at the highest level. The order is as follows: teamwork skills, interpersonal skills, communication skills and use of technology, analytical thinking skills, and creative thinking skills. 2) A comparison of the teachers’ opinions on the administrative skills of the school administrators in the 21st century, schools in the group of United Campus Ratchayothin under the Secondary Educational Service Area Office 2 which is classified by educational level and work experience. The results can be summarized as an overview and aspects of the teachers’ opinions had no different even though had different educational levels and different work experiences on the administrative skills of the school administrators in the 21st century was not a statistically significant difference.